17
$\begingroup$

Given that $z^2 + z + 1 = 0$ where $z$ is a complex number, how do I proceed in calculating $z^4 + \dfrac1{z^4}$?

Calculating the complex roots and then the result could be an answer I suppose, but it's not quite elegant. What alternatives are there?

$\endgroup$
36
$\begingroup$

From $z^2 + z + 1 = 0$, we have $$z +\frac{1}{z}=-1.$$ Taking square, we get $$z^2 +\frac{1}{z^2}+2=1,$$ which implies that $$z^2 +\frac{1}{z^2}=-1.$$ I think you will know what to do next.

$\endgroup$
  • $\begingroup$ I see... Thank you for the quick answer! $\endgroup$ – Mihai Bişog Jan 1 '12 at 11:54
  • 15
    $\begingroup$ $\displaystyle{z^{2^k}+\frac{1}{z^{2^k}}=-1}$ for all $k$. $\endgroup$ – Jonas Meyer Jan 1 '12 at 11:54
  • 1
    $\begingroup$ @Jonas: nice observation! $\endgroup$ – Paul Jan 1 '12 at 12:06
  • $\begingroup$ Dickson polynomials FTW! $\endgroup$ – Jyrki Lahtonen Jan 1 '12 at 14:20
  • 5
    $\begingroup$ Another way to justify that $z+\dfrac1{z}=-1$ is that due to the coefficient symmetry, if $z$ is a root, then $\dfrac1{z}$ is a root as well. By Vieta, then, the sum of those two roots ought to be the negative of the coefficient of the linear term... $\endgroup$ – J. M. is a poor mathematician Jan 1 '12 at 15:15
22
$\begingroup$

Essentially the same calculation also follows from the observation that $x^2+x+1=\phi_3(x)$ is the third cyclotomic polynomial. So $z^3-1=(z-1)(z^2+z+1)=0$, and hence $z^3=1$ for any solution $z$. Therefore $$ z^4+\frac{1}{z^4}=z\cdot z^3+\frac{(z^3)^2}{z^4}=z+z^2=-1. $$

$\endgroup$
  • 1
    $\begingroup$ Very clever! :D $\endgroup$ – J. M. is a poor mathematician Jan 1 '12 at 12:08
  • 9
    $\begingroup$ Very nice! If you had not posted this already, I would have used the sum of geometric series (instead of cyclotomic polynomials) to write $$0=z^2+z+1=\frac{z^3-1}{z-1}\Rightarrow z^3=1$$ and $$z^4+\frac{1}{z^4}=(z^3)z+\frac{1}{(z^3)z}=z+\frac{1}{z}=\frac{z^2+1}{z}=\frac{-z}{z}=-1.$$ $\endgroup$ – Dilip Sarwate Jan 1 '12 at 15:48
17
$\begingroup$

$$\begin{align*} z^4+\frac1{z^4}&=(-z-1)^2+\frac1{(-z-1)^2}\\ &=z^2+2z+1+\frac1{z^2+2z+1}\\ &=(-z-1)+2z+1+\frac1{(-z-1)+2z+1}\\ &=z+\frac1{z}=\frac{z^2+1}{z}=\frac{-z-1+1}{z}=-1 \end{align*}$$

$\endgroup$
  • 3
    $\begingroup$ What would be wrong with systematic reduction using the minimal polynomial? Nothing! $\endgroup$ – Jyrki Lahtonen Jan 1 '12 at 12:25
9
$\begingroup$

Here is an alternative approach: let's consider $z^{8}+1$ , and then divide by $z^{4}$.

By using geometric series, notice that $$z^{8}+z^{7}+z^{6}+z^{5}+z^{4}+z^{3}+z^{2}+z+1=\left(z^{2}+z+1\right)\left(z^{6}+z^{3}+1\right)=0.$$ Now, as $z^{2}+z+1=0$, we know that both $z^{7}+z^{6}+z^{5}=0$ and $z^{3}+z^{2}+z=0$, and hence $$z^{8}+z^{4}+1=0$$ so that $z^{8}+1=-z^{4}$. Thus, we conclude that $$z^{4}+\frac{1}{z^{4}}=-1.$$

$\endgroup$
5
$\begingroup$

Different people see different things in the relation $z^2+z+1=0$. Just as Jyrki did, I see the third cyclotomic polynomial. Its roots are $-1/2 \pm \sqrt{-3}/2$, the two primitive cube roots of unity. Call one of these $\omega$ and see that $\omega^3=1$, so that $\omega^4=\omega$ and $\omega^{-4}=\omega^2$. Their sum is $-1$, from the defining relation.

$\endgroup$
4
$\begingroup$

Hint $\ $ Exploit innate symmetry: for $\rm\ y = z^{-1} $ you know $\rm\ yz\ (=\: 1)\:$ and $\rm\ y+z\ (=\: z^{-1}\!+z\: =\: -1)\ $

Thus you know $\rm\ \ \ y^2 + z^2\ =\ (y\ +\ z)^2-\ 2\:(y\:z)$

hence you know $\rm\ y^4 + z^4\ =\ (y^2\! + z^2)^2 - 2\:(y\:z)^2$

For more on symmetric polynomials see the Wikipedia article on Newton's identities.

$\endgroup$
  • 6
    $\begingroup$ To downvoter: if something is not clear then please feel welcome to ask questions and I will be happy to elaborate. $\endgroup$ – Bill Dubuque Jan 1 '12 at 22:52
1
$\begingroup$

$$z^2+z+1=0$$ Clearly $z \not= 0$ and therefore $z+\dfrac{1}{z}=-1.$ Note that $$z^{n+1}+\frac{1}{z^{n+1}}=\left(z+\frac{1}{z}\right)\left(z^n+\frac{1}{z^n}\right)-\left(z^{n-1}+\frac{1}{z^{n-1}}\right).$$ Therefore if we define the function $U:\Bbb{N}\cup\{0\} \to \Bbb{C}$ as $$U_n=z^n+\frac{1}{z^n}$$ then we have $U(0)=2,$ $U(1)=-1$ and $$U(n+1)+U(n)+U(n-1)=0\,\,\,\,\,\,\,\,\,\forall n \in \Bbb{N}.$$
Using this recurrence you can calculate $z^n+\dfrac{1}{z^n}$ for any $n \in \Bbb{N}.$

Alos you can follow this approach.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.